(3CHjGJ ef hajGJ GHf GdNWjH GdbSfWjfjs - (3eMeO Hf Ydj Hf GdaTJGdj GdeZQHj,(B1021 (3g`s
(3ChdgG (B:s
(3CMH QShd Gddg Ke YKjbg dg MLH aj GdceGd GdeSQHd s
(3BNQgG (B:s
(3hdLh HMQ Yde PGc GHf XGgQ aJMhG Hg bdHj PgGH Hf eQSd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GHf GdNWjH GdbSfWjfj gh CMeO Hf Ydj Hf GdNWjH GHf bfaO GdbSfWjfj GdeZQHj GdTgjQ H` GHf GdNWjHs
(3GdeJhai (B810(3g`s
(3eYLe GdeDdajf (B205/1s
(3GHf GdbGVj GdecfGSj gh CMeO Hf eMeO Hf eMeO Hf CMeO Hf Ydjs
(3hjYQa HGHf GdbGVjs
(3GdeJhai (B1025(3g`s
Keywords: (3GdCOHs